Bedding-parallel calcite veins as a proxy for shale reservoir quality. (May 2021) - Zhang, Jianguo; Jiang, Zaixing; Wang, Siqi; Wang, Ruyue; Zhang, Yuanfu; Du, Wei
Abstract: The Ordovician-Silurian Sichuan, Eocene Bohai Bay and Eocene Nanxiang Basins have been the main productive basins of shale oil and gas in China. Bedding-parallel calcite veins-bearing intervals are found to coincide with the shale gas- and/or shale oil-producing layers. Bedding-parallel calcite veins-bearing shale intervals are demonstrated to be always overpressured, organic-rich, mature and brittle, and they generally have higher porosity, higher permeability and higher gas/oil content than adjacent layers. A systematic study on the genetic mechanism of these veins confirms that the above phenomenon is prevalent in the three above mentioned basins and other sedimentary basins. Bedding-parallel calcite veins are viewed as a proxy for shale reservoir quality. This proxy helps geologists to preliminarily determine the potential shale reservoir layers out of the thick shale successions before systematic organic-inorganic tests, because it can be easily identified in cores, outcrops and well logs, thereby contributing to economic and time-efficient exploration. Therefore, occurrence of bedding-parallel calcite veins in shale reservoir exploration needs further attention, especially in petroliferous basins where shale reservoir exploration is still in its infancy. Highlights: Bedding-parallel calcite veins are formed during mature hydrocarbon generation. Bedding-parallel calcite veins are linked the key elements in shale reservoir evaluation.